Comparison of Distance and Angular Analysis for Measurement of Hamstring Flexibility in Preschoolers - Anke Hua; Jingyuan Bai; Yong Fan; Jian Wang (MDPI AG, 2022)
The study aimed to (1) investigate the reliability and usefulness of a proposed angular analysis during a modified sit-and-reach (MSR) test, and (2) compare the proposed MSR angular analysis and the commonly used MSR distance to verify the influence of the anthropometric characteristics in preschoolers. 194 preschoolers participated in the study. Before testing, the anthropometric characteristics were collected. Each participant performed the MSR test twice. The MSR distance score was obtained from the starting point to the reaching point, while the MSR angle score was calculated according to the approximate hip flexion angle. Both the relative and absolute reliability were good for the angular analysis during an MSR test in preschoolers (ICC ranging from 0.82 to 0.91, CV% ranging from 8.21 to 9.40). The angular analysis demonstrated good usefulness, with a lower typical error than the smallest worthwhile change in 3- and 5-year-old groups. The MSR angle scores could eliminate the concern of the influence of anthropometric characteristics, while MSR distance and anthropometric characteristics (i.e., sitting height and arm length) were found to be weakly correlated. In conclusion, the angular analysis when performing the MSR test is reliable and appears to eliminate the concern regarding the limb length bias.